2011
DOI: 10.1111/j.2044-8333.2010.02007.x
|View full text |Cite
|
Sign up to set email alerts
|

The linking of burglary crimes using offender behaviour: Testing research cross‐nationally and exploring methodology

Abstract: Purpose.The current study tests whether existing behavioural case linkage findings from the United Kingdom (UK) will replicate abroad with a sample of residential burglaries committed in Finland. In addition, a previously discussed methodological issue is empirically explored. Methods.Seven measures of behavioural similarity, geographical proximity and temporal proximity are calculated for pairs of burglary crimes committed by 117 serial burglars in Finland. The ability of these seven measures to distinguish b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 27 publications
8
64
1
1
Order By: Relevance
“…Hypotheses: In accordance with previous studies involving serial sexual offences (Grubin et al , ; Santtila et al , ; Wilson et al , ), we expected to extract stable behavioural scales or dimensions that could be used as predictors of linkage status to achieve correct classification above chance, using the LOOCV method. With the empirical evidence (Salo et al , ), the multivariate behavioural approach through a NBC would be expected to outperform a dimensional approach in terms of error‐free classification above chance, using the LOOCV method. As a more realistic test (as suggested by Woodhams & Labuschagne, ), we expected both approaches to perform significantly worse in terms of correct classifications when non‐serial cases are included in the linking task (although in Tonkin, Santtila et al , ; Tonkin, Woodhams, et al , , the sample constellation did not appear to negatively influence the linking performance in serial and one‐off burglaries). Calculating a percentage of error free links imposes an artificial decision threshold (Bennell et al , ). Therefore, it was assumed that dimensional and multivariate behavioural linking would achieve similar linkage accuracies when evaluated through ROC analysis.…”
Section: Assumptions and Support Of Linkage Analysissupporting
confidence: 52%
See 1 more Smart Citation
“…Hypotheses: In accordance with previous studies involving serial sexual offences (Grubin et al , ; Santtila et al , ; Wilson et al , ), we expected to extract stable behavioural scales or dimensions that could be used as predictors of linkage status to achieve correct classification above chance, using the LOOCV method. With the empirical evidence (Salo et al , ), the multivariate behavioural approach through a NBC would be expected to outperform a dimensional approach in terms of error‐free classification above chance, using the LOOCV method. As a more realistic test (as suggested by Woodhams & Labuschagne, ), we expected both approaches to perform significantly worse in terms of correct classifications when non‐serial cases are included in the linking task (although in Tonkin, Santtila et al , ; Tonkin, Woodhams, et al , , the sample constellation did not appear to negatively influence the linking performance in serial and one‐off burglaries). Calculating a percentage of error free links imposes an artificial decision threshold (Bennell et al , ). Therefore, it was assumed that dimensional and multivariate behavioural linking would achieve similar linkage accuracies when evaluated through ROC analysis.…”
Section: Assumptions and Support Of Linkage Analysissupporting
confidence: 52%
“…This methodology, which was utilised by Santtila et al (), tests the accuracy of offence–offender or offence–series combinations. It therefore differs from the more commonly used methodology put forward by Bennell (2002, cited in Tonkin, Santtila et al , ; Tonkin, Woodhams, et al , ) where logistic regression analysis is used to calculate the probability of a correct link for all possible offence pairs (i.e. offence–offence combinations).…”
Section: Methodsmentioning
confidence: 98%
“…Comparable ranges for burglary were reported by Markson, Woodhams, and Bond (), Melnyk et al . (), and Tonkin, Santtila, and Bull () (interestingly, levels of linking accuracy in Finnish burglaries appear to be substantially higher; Tonkin, Santtila et al ., ). The AUC ranges in studies of car theft are also very wide (0.54–0.93 in Davies et al ., ; 0.56–0.81 in Tonkin et al ., ; and 0.50–0.82 in Tonkin, Woodhams, Bull, Bond, & Santtila, ), as is the range in the lone study of personal robbery (0.45–0.92; Burrell et al ., ).…”
Section: Resultsmentioning
confidence: 89%
“…For example, when Tonkin, Santtila et al . () examined linking accuracy in a sample of Finnish residential burglaries, they found that the level of accuracy was greater than that observed in previous UK‐based research. As Tonkin () states, ‘… the AUC value for all MO behaviours in Finland was 0.72 (which compared to an average AUC value in UK‐based research of 0.65), the AUC value for the target domain in Finland was 0.73 (compared to a UK average of 0.60), and the AUCs for entry and internal behaviours were both 0.66 (compared to UK averages of 0.58 and 0.51, respectively)’ (p. 13).…”
Section: Resultsmentioning
confidence: 91%
“…These were included because they have proved to be useful predictors of linkage in previous research (e.g., Tonkin, Santtila, & Bull, 2012). Furthermore, an analyst survey (Burrell & Bull, 2011) revealed that the majority of analysts (15 out of 18) use spatial and temporal behaviours to support linkage decisions.…”
Section: Behavioural Domain Formationmentioning
confidence: 99%